Electron cyclotron emission simulation from TCABR plasmas - Lyvio,Eduardo H. (2004)
Electron cyclotron emission due to electrons described by a particular distribution function has been studied. The latter presents an extended tail generated by the interaction of the Lower Hybrid wave with the plasma as compared to the Maxwellian distribution function. For this purpose a new code has been developed which calculates for an arbitrary distribution function the intensity of radiation arriving at the plasma edge, the emission profile (as a function of position) and the optical depth (as a function of frequency) using the full dielectric tensor for a magnetized plasma. The electron distribution function is obtained by solving the Fokker-Planck equation in the frame of the quasilinear theory using a slab model. Results obtained for TCABR-like parameters show changes in the emission localized at positions where electron distribution function has been modified by the waves. Main parameter governing the changes in the electron cyclotron emission is the wave power. Changes in the plasma temperature and density profiles do not alter the emission profiles substantially. Reconstructed electron temperature profile has been obtained from the code radiation emission simulation, showing good agreement with the imposed temperature profile. The present results also showed that the changes in the emission profile in the region where the Lower Hybrid wave deposes its energy as compared with the emission profile of the plasma with Maxwellian distribution function are not so strong.